Measuring the quality of perioperative care in cardiac surgery. - Coulson, T.; Mullany, D.; Reid, Christopher; Bailey, M.; Pilcher, D. (2017)
Quality of care is of increasing importance in health and surgical care. In order to maintain and improve quality, we must be able to measure it and identify variation. In this narrative review, we aim to identify measures used in the assessment of quality of care in cardiac surgery and to evaluate their utility. The electronic databases Pubmed/MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), Cochrane Database of Systematic Reviews, and CINAHL were searched for original published studies using the terms 'cardiac surgery' and 'quality or outcome or process or structure' as either keywords in the title or text or MeSH terms. Secondary searches and identification of references from original articles were carried out. We found a total of 54 original articles evaluating measurements of quality. While structure, process, and outcome indicators remain the mainstay of quality measurement, new and innovative methods of risk assessment have improved reliability and discrimination. Continuous assessment provides a promising method of both maintaining and improving quality of care. Future studies should focus on long-term and patient-centred outcomes, such as quality-of-life measures.